Human–wildlife coexistence in a changing world. Issue 4 (14th May 2020) - König, Hannes J.; Kiffner, Christian; Kramer‐Schadt, Stephanie; Fürst, Christine; Keuling, Oliver; Ford, Adam T.
Abstract: Human–wildlife conflict (HWC) is a key topic in conservation and agricultural research. Decision makers need evidence‐based information to design sustainable management plans and policy instruments. However, providing objective decision support can be challenging because realities and perceptions of human–wildlife interactions vary widely between and within rural, urban, and peri‐urban areas. Land users who incur costs through wildlife argue that wildlife‐related losses should be compensated and that prevention should be subsidized. Supporters of human–wildlife coexistence policies, such as urban‐dwelling people, may not face threats to their livelihoods from wildlife. Such spatial heterogeneity in the cost and benefits of living with wildlife is germane in most contemporary societies. This Special Section features contributions on wildlife‐induced damages that range from human perspectives (land use, psychology, governance, local attitudes and perceptions, costs and benefits, and HWC and coexistence theory) to ecological perspectives (animal behavior). Building on current literature and articles in this section, we developed a conceptual model to help frame HWC and coexistence dimensions. The framework can be used to determine damage prevention implementation levels and approaches to HWC resolution. Our synthesis revealed that inter‐ and transdisciplinary approaches and multilevel governance approaches can help stakeholders and institutions implement sustainable management strategies that promote human–wildlife coexistence. Abstract : Article impact statement : Integrated and participatory research are needed to provide the evidence base to address human–wildlife conflict and coexistence. Abstract : Coexistencia Humano – Vida Silvstre en un Mundo Cambiante Resumen: El conflicto humano – vida silvestre (HWC) es un tema muy importante para la investigación agrícola y de la conservación. Los tomadores de decisiones necesitan información basada en evidencias para diseñar planes de manejo sustentable e instrumentos políticos. Sin embargo, proporcionar un apoyo objetivo para las decisiones puede ser un reto ya que las realidades y percepciones de las interacciones humano – vida silvestre varían enormemente entre y dentro de las áreas rurales, urbanas y peri‐urbanas. Los usuarios de terrenos que incurren en costos debido a la vida silvestre argumentan que las pérdidas relacionadas a la vida silvestre deberían ser compensadas y que la prevención debería estar subsidiada. Es probable que quienes apoyan las políticas de coexistencia entre humanos y vida silvestre, como los habitantes de zonas urbanas, no enfrenten una amenaza a su medio de subsistencia debido a la vida silvestre. Dicha heterogeneidad espacial en el costo y beneficio de cohabitar con la vida silvestre es relevante en la mayoría de las sociedades contemporáneas. Esta Sección Especial presenta contribuciones sobre daños inducidos por vida silvestre que van desde las perspectivas humanas (uso de suelo, psicología, gobierno, actitudes y percepciones locales, costo y beneficio y la teoría del conflicto y la coexistencia humano‐vida silvestre) hasta las perspectivas ecológicas (comportamiento animal). A partir de los artículos y la literatura actuales en esta sección desarrollamos un modelo conceptual para ayudar a estructurar los alcances del HWC y de la coexistencia. El marco de trabajo puede usarse para determinar los niveles y estrategias de implementación de la prevención del daño a la solución del conflicto humano ‐ fauna. Nuestra síntesis reveló que las estrategias inter‐ y transdisciplinarias y las estrategias de gobierno multiniveles pueden ayudar a que los actores y las instituciones implementen estrategias de manejo sustentable para promover la coexistencia entre los humanos y la vida silvestre. 摘要: 人类与野生动物的冲突是保护研究和农业研究的一个重要问题。决策者需要基于证据的信息来设计可持续的管理计划和政策工具。然而, 由于农村、城市和城郊之内或之间的人类与野生动物相互作用的现实情况和观念存在很大差异, 因此提供客观的决策支持也面临着挑战。因野生动物而遭受损失的土地使用者认为, 与野生动物相关的损失应该得到补偿, 且实施保护措施也应得到补贴。人与野生动物共存政策的支持者, 如城市居民, 则可能不会面临野生动物对生计的威胁。这种与野生动物共存的成本和收益的空间异质性普遍存在于多数当代社会。本专题包含介绍野生动物所造成破坏的系列文章, 研究的角度从人类视角 (土地利用、心理、管理、当地态度和观念、成本和收益、人类与野生动物的冲突和共存理论) 到生态视角 (动物行为) 。基于已有文献和本专题的文章, 我们设计了一个概念模型来为人类与野生动物共存及共存的维度制定框架。该框架可用于确定预防野生动物造成破坏的实施水平及解决人类与野生动物冲突的方法。我们的综合分析表明, 跨学科和多级管理方法可以帮助利益相关者和机构实施可持续管理策略, 促进人类与野生动物的共存。 【翻译: 胡怡思; 审校: 聂永刚】